Design and Function Evaluation of Line Follower Plant Sprayer Robot - Sutisna, Setya Permana; Siregar, Tika Hafzara; Ahmad, Anton Royanto (Master Program in Mechanical Engineering, Gunadarma University, 2023)
Agriculture tools necessary for increasing food security in Indonesia. An automatic spraying for plant became one of the tool that help in pot plant maintenance. This study was developing a prototype of automatic line follower robot for spraying plant. Designing a new construction and adding a line follower sensor, this robot could move between plant pots with guidance of black line. Main chassis of this robot made from 3 mm aluminum plate with 50 cm length and 20 cm width. Control of this robot using Arduino Uno as microcontroller that could control the movement of the robot and also could control movement of nozzle and flow rate. Performance testing of this robot held inside the room with concrete floor and placed on the white fabric with black line as a guidance and sign to stop and spray. As the result, average linier speed for this robot was 0,7 m/s and flow rate for spraying was 8,9 ml/s with 89,5% accuracy.